THE CONCEPT OF "CONTEMPTUS MUNDI" IN "ŚWIAT POGARDZONY…" (THE WORLD DESPISED…, 1647) BY STANISŁAW TEODOR PIOTRKOWCZYK - Kaczor-Scheitler, Katarzyna (Prace Polonistyczne, 2025)
The seventeenth-century devotional epithalamium Świat pogardzony od Jej Mości Panny Kunegundy Piotrkowczykówny […] krótko opisany (The world despised by her noble mistress Cunigunde Piotrkowczyk […] briefly described) by Stanisław Teodor Piotrkowczyk (c. 1625–1674/75), a poet and printer from Kraków, was written for the ceremony of taking the veil by his sister Agnieszka Piotrkowczyk (she joined the Kraków Dominican Order and took the name Cunigunde). The epithalamium centres on a panegyric theme. The addressee is praised for her choice of monastic life and virtues. The author argues that the only path to happiness lies in consecrated life, which frees a human being from the illusory temptations of the world and helps them come closer to God. Piotrkowczyk incorporated elements of the Christian and ancient traditions into his work. Intertwined, they set the stage for the event that the writer intended to immortalize, as well as for the laudatory purpose of the occasional poem. The references to antiquity in Świat pogardzony… (The World Despised…) show that the author clearly alludes to trends that were popular at the time, using traditional imagery. However, in Piotrkowczyk’s poem mythological characters stand in opposition to biblical figures, with Christian values taking precedence. Poetry grants immortality to those it celebrates. The author of Świat pogardzony… (The World Despised…) bestows a mark of immortality upon his sister – the addressee of the text. Moreover, the publication of the occasional poem contributed to Piotrkowczyk’s own fame.